The lieutenant's nurse - Ackerman, Sara (Mira, 2019)
"She's never even seen the ocean before, but Eva Cassidy has her reasons for making the crossing to Hawaii, and they run a lot deeper than escaping a harsh Michigan winter. Newly enlisted as an Army Corps nurse, Eva is stunned by the splendor she experiences aboard the steamship SS Lurline; even more so by Lt. Clark Spencer, a man she is drawn to but who clearly has secrets of his own. But Eva's past--and the future she's trying to create--means that she's not free to follow her heart. Clark is a navy intelligence officer, and he warns her that the United States won't be able to hold off joining the war for long, but nothing can prepare them for the surprise attack that will change the world they know. In the wake of the bombing of Pearl Harbor, Eva and her fellow nurses band together for the immense duty of keeping the American wounded alive. And the danger that finds Eva threatens everything she holds dear. Amid the chaos and heartbreak, Eva will have to decide whom to trust and how far she will go to protect those she loves"--